MENINGKATKAN KETERAMPILAN BERCERITA DENGAN MENGGUNAKAN MEDIA GAMBAR SISWA KELAS IV SEKOLAH DASAR - Riniati, Waode (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2022)
Improving storytelling skills using image media by the students of grade IV at SD Negeri 101 Buton. The purpose of this study was to describe storytelling skills using picture media in grade IV SD Negeri 101 Buton. The formulation of the problem in this research is how to improve storytelling skills through the using of image media for grade IV students of SD Negeri 101 Buton. This is motivated by the low skills of students in storytelling, as well as the difficulty of students in expressing the contents of their thoughts in the form of words and sentences. This research was a Classroom Action Research. Research subjects in grade IV SD Negeri 101 Buton in the 2020/2021 school year there are 26 students consisting 0f 14 male students and 12 female students. This classroom action research was conducted in two cycles. Classical student learning indicators have reached 75%. Based on the research results, it can be concluded that the using of image media can inmprove storytelling skills. In the pre-cycle stage, the percentage of completeness of students has reached 34,61%, in cycle I the percentage of completeness of students reached 53,85% and in cycle II had reached a percentage of completeness of 80,77%.Based on the learning outcomes as well as teacher and student activities, it can be concluded that using image media can improve the storytelling skills of grade IV students of SD Negeri 101 Buton.